On the Non-commutative Neutrix Product of the Distributions δ ^(r)(x) and x^-s^m|x| - Fisher, Brian; Ege, Inci; Özçag, Emin (Sarajevo Journal of Mathematics, 2024)
It is proved that the non-commutative neutrix product of the distributions δ ^(r)(x) and x^-s ^m|x| exists and δ ^(r)(x) ° x^-s ^m |x| = 0 for r,m=0,1,2, … and s = 1,2, …. 2000 Mathematics Subject Classification. 46F10